Application of Interactive Digital Book-Assisted Discovery Learning to Improve Mathematics Learning Outcomes of Grade IV Elementary School Students - Triwahyuningtyas, Dyah; Sofiya , Siti Nuryatus; Setyaningsih, Yuyun (Didactica : Jurnal Kajian Pendidikan dan Pembelajaran, 2025)
This study aims to improve students' mathematics learning outcomes through the application of the Discovery Learning model assisted by interactive digital books on the topic of flat shapes. The research was motivated by the low achievement of learning completeness among grade IV students at Bakalan Krajan 1 Public Elementary School, Malang, primarily due to conventional teaching methods that lacked student engagement. The study involved 28 fourth-grade students and employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart spiral design, conducted over two cycles. Each cycle included the stages of planning, action implementation, observation, and reflection. Data were collected through learning outcome tests administered at each meeting, and analyzed quantitatively using descriptive statistics to determine the percentage of learning completeness. The results indicated a steady improvement in learning outcomes, with completeness increasing from 53.5% in the first meeting of Cycle I to 60.7% in the second meeting. In Cycle II, the percentage rose significantly to 78.5% in the first meeting and reached 85.7% by the second. These findings demonstrate that the Discovery Learning model, supported by interactive digital books, effectively enhances students’ mathematics learning outcomes by promoting active participation in the learning process. However, the study's limitations include a relatively short implementation period and a small sample limited to one class.